Endoplasmic Reticulum Associated Aminopeptidase 2 (ERAP2) Is Released in the Secretome of Activated MDMs and Reduces in vitro HIV-1 Infection - Irma Saulle; Salomè Valentina Ibba; Enrica Torretta; Cecilia Vittori; Claudio Fenizia; Federica Piancone; Davide Minisci; Elisa Maria Lori; Daria Trabattoni; Cecilia Gelfi; Cecilia Gelfi; Mario Clerici; et al. (Frontiers in Immunology, 2019)
Background: Haplotype-specific alternative splicing of the endoplasmic reticulum (ER) aminopeptidase type 2 (ERAP2) gene results in either full-length (FL, haplotype A) or alternatively spliced (AS, haplotype B) mRNA. HapA/HapA homozygous (HomoA) subjects show a reduced susceptibility to HIV-1 infection, probably secondary to the modulation of the antigen processing/presenting machinery. ERAP1 was recently shown to be secreted from the plasma membrane in response to activation; we investigated whether ERAP2 can be released as well and if the secreted form of this enzyme retains its antiviral function.Methods: Human monocyte derived macrophages (MDMs) were differentiated from peripheral blood mononuclear cells (PBMCs) isolated from 6 HomoA healthy controls and stimulated with IFNγ and LPS. ERAP2-FL secretion was evaluated by mass spectrometry. PBMCs (14 HomoA and 16 HomoB) and CD8-depleted PBMCs (CD8−PBMCs) (4 HomoA and 4 HomoB) were in vitro HIV-infected in the absence/presence of recombinant human ERAP2-FL (rhERAP2) protein; p24 viral antigen quantification was used to assess viral replication. IFNγ and CD69 mRNA expression, as well as the percentage of perforin-producing CD8+ T Lymphocytes, were analyzed 3 and 7-days post in vitro HIV-1-infection, respectively. The effect of rhERAP2 addition in cell cultures on T cell apoptosis, proliferation, activation, and maturation was evaluated as well on 24 h-stimulated PBMCs.Results: ERAP2 can be secreted from human MDMs in response to IFNγ/LPS stimulation. Notably, the addition of rhERAP2 to PBMC and CD8−PBMC cultures resulted in the reduction of viral replication, though these differences were statistically significant only in PBMCs (p < 0.05 in both HomoA and HomoB). This protective effect was associated with an increase in IFNγ and CD69 mRNA expression and in the percentage of perforin-expressing CD107+CD8+ cells. RhERAP2 addition also resulted in an increase in CD8+ activated lymphocyte (CD25+HLA−DRII+) and Effector Memory/Terminally differentiated CD8+ T cells ratio.Conclusions: This is the first report providing evidence for the release of ERAP2 in the secretome of immunocompetent cells. Data herein also indicate that exogenous ERAP2-FL exerts its protective function against HIV-1 infection, even in HomoB subjects who do not genetically produce it. Presumably, this defensive extracellular feature is only partially dependent on immune system modulation.